Salishan materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Ransom, Jay Ellis, 1914-; Siddle, Julia; Swadesh, Morris, 1909-1967; Jacobs, Melville, 1902-1971; Collins, June M.; Kinkade, M. Dale (Marvin Dale), 1933-; Newman, Stanley S. (Stanley Stewart), 1905-1984 (1936)
Several items relating to the Salishan languages have been identified in the C. F. Voegelin Papers. Nearly all are located in Subcollection II. There is relevant correspondence with M. Dale Kinkade (regarding a comparative work on color and anatomical terms in Salish, Navajo, and English), Stanley Newman (mentioning his recent work on Bella Coola and comparative Salish), and Jay Ellis Ransom (his work on Salish languages, Duwamish, Aleut, Flathead) in Series I. Correspondence. Series II. Research Notes, Subseries VIII. Undetermined Phylum Affiliation. These materials are in folders labeled as follows: "Mosan" [Voegelin originally labeled this folder "Mosan = Salish + Wakashan + Chimakuan = Quileute"]; "Salish"; "Salish: Bella Coola (Nuxalk), Coeur d'Alene"; "Salish: Duwamish" [these materials are attributed to Jay Ellis Ransom and include texts in Salish and English, with linguistic analysis, recorded from Mrs. Julia Siddle on the Muckleshoot Reservation in 1936]; and "Salish problem." This last folder contains correspondence compiled by Voegelin revolving around the "Salish Problem," including letters from Morris Swadesh (on analysis of Salish material by Boas and James Teit in the ACLS collection), June Collins, Melville Jacobs. This folder also includes draft of a paper on Salish languages based upon the discussion in these letters. The final Salish item is located in Series IV. Works by Others and consists of Jay Ellis Ransom's "Pronomial System in Duwamish Salish" (1945). Researchers should also view the entries for specific Salishan languages.